Pengaruh Pemberian Kombinasi Fermentasi Air Cucian Beras dan Limbah Cair Tahu pada Pertumbuhan dan Hasil Tanaman Cabai Rawit (Capsicum frutescens L.) Varietas Pelita F1 - Namira Fahira Azhari; Muharam Muharam; Hayatul Rahmi (Peneliti.net, 2021)
This research was conducted at the screen house on Pancawati Village, Klari District, Karawang Regency, West Java from January to April 2021. The research method used is an experimental method with a single factor Randomized Block Design (RBD) with 9 combinations of treatments and 3 replications, the treatments: A (fermentation of rice water 0%+ tofu liquid waste 0%), B (fermentation of rice water 0%+ tofu liquid waste 10%), C (fermentation of rice water 0%+ tofu liquid waste 20%), D (fermentation of rice water 50%+ tofu liquid waste 0%), E (fermentation of rice water 50%+ tofu liquid waste 10%), F (fermentation of rice water 50%+ tofu liquid waste 20%), G (fermentation of rice water 100%+ tofu liquid waste 0%), H (fermentation of rice water 100%+ tofu liquid waste 10%), I (fermentation of rice water 100%+ tofu liquid waste 20%). The result showed there was significant on fermentation of rice water and tofu liquid waste on the average height of plants 7 hst, the number of leaves 28 hst, the number of branches 28 hst, and the area of leaves. The treatment of E (fermentation of rice water 50%+ tofu liquid waste 10%) obtained the best result the average height of plants 7 hst, the number of leaves 28 hst and the number of branches 28 hst meanwhile treatment B (fermentation of rice water 0%+ tofu liquid waste 10%) obtained the best result the average leaf area.